Being Tamil, being Hindu: Tamil migrants' negotiations of the absence of Tamil Hindu spaces in the West Midlands and South West of England. Issue 1 (2nd January 2016) - Jones, Demelza
Abstract: This paper considers the religious practices of Tamil Hindus who have settled in the West Midlands and South West of England in order to explore how devotees of a specific ethno-regional Hindu tradition with a well-established UK infrastructure in the site of its adherents' population density adapt their religious practices in settlement areas which lack this infrastructure. Unlike the majority of the UK Tamil population who live in the London area, the participants in this study did not have ready access to an ethno-religious infrastructure of Tamil-orientated temples 1 and public rituals. The paper examines two means by which this absence was addressed as well as the intersections and negotiations of religion and ethnicity these entailed: firstly, Tamil Hindus' attendance of temples in their local area which are orientated towards a broadly imagined Hindu constituency or which cater to a non-Tamil ethno-linguistic or sectarian community; and, secondly, through the 'DIY' performance of ethnicised Hindu ritual in non-institutional settings.